A Comparative Study between Self-Controlled Energetic Neuro: Adaptive Regulator (SCENAR) and Commercially Available Equipment in the Management of Orofacial Pain - KP Mahesh; M Aparna Vijayan (Wolters Kluwer Medknow Publications, 2024)
Background: SCENAR[™] is a noninvasive neuroadaptive device which works on biofeedback mechanism. A case-control study was conducted on 24 patients of either sex with age group between 20 and 35 years of which 12 patients were diagnosed with trigeminal neuralgia and 12 with TMJ pain. Aims: To compare the effectiveness of SCENAR[™] and commercially available similar equipment in management of trigeminal neuralgia and TMJ pain. Objective: To assess the efficacy of SCENAR[™] in management of trigeminal neuralgia and TMJ pain. Methods: Diagnostic criteria for trigeminal neuralgia and TMJ pain were taken into consideration. The patients were divided into test and control groups. SCENAR[™] was used in the test group, and commercially available similar equipment was used in the control group. Pre- and post-treatment pain were recorded using the visual analogue scale. Statistical analysis was done using Chi-square tests (Pearson Chi-square test and Fisher's exact test). Results: The patient group treated with SCENAR[™] showed significant improvement in pain when compared to the control group. The patient group with trigeminal neuralgia showed an effective pain reduction of 79.12% and the patient group with TMJ pain showed 67.65% of pain reduction. Conclusion: The results obtained from our present study showed that we can incorporate SCENAR[™] as a treatment modality in the management of orofacial pain as it has fewer side effects and more patient compliance.